Building capacity and capability for science diplomacy: challenges in decolonizing the curriculum for Global Health System Leadership - Millar, Ross; Abu-Agla, Ayat; Badr, Elsheikh (Frontiers in Public Health, 2025)
Education policy is the front and center of contemporary science diplomacy. This is particularly the case in global health where nation-states are being called upon to equip their health workforce with leadership skills and competencies to improve population health and engage in health system development. In the perspective that follows, we argue that successfully meeting such demands requires not only a high-quality education offering but also one that is aware of and engaged with the coloniality underpinning its underlying assumptions. This perspective makes two significant contributions to further understanding of this area. First, it shares the challenges being faced in developing an education offer for Global Health System Leadership at an International Branch Campus (IBC). Second, it provides an overview of how we are proactively seeking to overcome these challenges. The perspective argues that by engaging in a spirit of dialog and reflexivity, there is scope for decolonizing education science diplomacy.